"\\displaystyle\\textsf{True}\\\\\n\n\n\\sqrt{p} + \\sqrt{q} = 2x\\\\\n\n\n\\sqrt{q} = 2x - \\sqrt{p} = a\\\\\n\n\n\\sqrt{q} = a, q = a^2\\\\\n\n2x - \\sqrt{p} = a\\\\\n\n\\sqrt{p} = 2x - a\\\\\n\np = (2x - a)^2\\\\\n\n\n\\mathrm{d}z = p\\,\\mathrm{d}x + q\\,\\mathrm{d}y\\\\\n\n\n\\mathrm{d}z = (2x - a)^2\\,\\mathrm{d}x + a^2\\,\\mathrm{d}y\\\\\n\n\\int \\,\\mathrm{d}z = \\int (2x - a)^2\\,\\mathrm{d}x + \\int a^2\\,\\mathrm{d}y\\\\\n\n\nz = \\frac{(2x - a)^3}{6} + a^2y + b\\\\\n\n\\textsf{Therefore, it is true.}"
Comments
Leave a comment